Regulation of Arterial Reactivity by Concurrent Signaling through the E-Prostanoid Receptor 3 and Angiotensin Receptor 1 - Kraemer, Maria P. (Vascul Pharmacol, 2016)
Prostaglandin E(2) (PGE(2)), a cyclooxygenase metabolite that generally acts as a systemic vasodepressor, has been shown to have vasopressor effects under certain physiologic conditions. Previous studies have demonstrated that PGE(2) receptor signaling modulates angiotensin II (Ang II)-induced hypertension, but the interaction of these two systems in the regulation of vascular reactivity is incompletely characterized. We hypothesized that Ang II, a principal effector of the renin-angiotensin-aldosterone system, potentiates PGE(2)-mediated vasoconstriction. Here we demonstrate that pre-treatment of arterial rings with 1 nM Ang II potentiated PGE(2)-evoked constriction in a concentration dependent manner (AUC(−Ang II) 2.778 ± 2.091, AUC(+Ang II) 22.830 ± 8.560, ***P<0.001). Using genetic deletion models and pharmacological antagonists, we demonstrate that this potentiation effect is mediated via concurrent signaling between the angiotensin II receptor 1 (AT1) and the PGE(2) E-prostanoid receptor 3 (EP3) in the mouse femoral artery. EP3 receptor-mediated vasoconstriction is shown to be dependent on extracellular calcium in combination with proline-rich tyrosine kinase 2 (Pyk2) and Rho-kinase. Thus, our findings reveal a novel mechanism through which Ang II and PGE(2) regulate peripheral vascular reactivity.